Quantifying the effects of acute hypoxic exposure on exercise performance and capacity: A systematic review and meta-regression - Deb, S. K.; Brown, D. R.; Gough, L. A.; Mclellan, C. P.; Swinton, P. A.; Sparks, S. A.; Mcnaughton, L. R. (European Journal of Sport Science, 2018)
Objective: To quantify the effects of acute hypoxic exposure on exercise capacity and performance, which includes continuous and intermittent forms of exercise. Design: A systematic review was conducted with a three-level mixed effects meta-regression. The ratio of means method was used to evaluate main effects and moderators providing practical interpretations with percentage change. Data sources: A systemic search was performed using three databases (Google scholar, PubMed and SPORTDiscus). Eligibility criteria for selecting studies: Inclusion was restricted to investigations that assessed exercise performance (time trials (TTs), sprint and intermittent exercise tests) and capacity (time to exhaustion test, TTE) with acute hypoxic (<24 h) exposure and a normoxic comparator. Results: Eighty-two outcomes from 53 studies (N?=?798) were included in this review. The results show an overall reduction in exercise performance/capacity -17.8 ± 3.9% (95% CI -22.8% to -11.0%), which was significantly moderated by -6.5 ± 0.9% per 1000 m altitude elevation (95% CI -8.2% to -4.8%) and oxygen saturation (-2.0 ± 0.4%; 95% CI -2.9% to -1.2%). TT (-16.2 ± 4.3%; 95% CI -22.9% to -9%) and TTE (-44.5 ± 6.9%; 95% CI -51.3% to -36.7%) elicited a negative effect, whilst indicating a quadratic relationship between hypoxic magnitude and both TTE and TT performance. Furthermore, exercise less than 2 min exhibited no ergolytic effect from acute hypoxia.